Community Empowerment and Marketing in The Business of Bang Isra Pletok Beer Products in Betawi Cultural Village Setu Babakan - Pradini, Gagih; Hendratoni, Tonny; Azahari, Azril (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
Indonesia is rich in cultural diversity, namely the many. Each region in Indonesia has its own distinctive cuisine. Pletok beer or Betawi beer is a typical drink of the Betawi community that has existed since the Dutch colonial era. Pletok beer was created by natives who were inspired when they saw Europeans living in Jakarta at that time who used to drink beer to warm their bodies. Although named Pletok beer, this drink does not contain alcohol so it is not intoxicating. In this research activity, one of the typical Betawi beverage products has been taken, namely Pletok Bang Isra Beer which is located in Srengseng Sawah, Jagakarsa District, South Jakarta City. Pletok Bang Isra beer beverage products are one of the materials for on-site observation and can directly find out community empowerment and marketing in the Pletok Bang Isra Beer beverage product business